Comparison of short-term memory between stunting and non-stunting children in urban and rural elementary school students in Kupang 2019 - Wahda Dwi Sari; Christina Olly Lada; Rr. Listyawati Nurina; Maria Agnes Etty Dedy (Indonesian Nutrition Association, 2020)
Background: Inadequate chronic nutrition can cause disruption of bone growth and brain development. Impaired bone growth can cause stunting in children, and a disruption of brain development will affect cognitive function, one of them is short-term memory. This study aimed to compare the short-term memory between stunting and non stunting in urban and rural elementary school students in Kupang.Methods: This research used analytic observational method with cross sectional design conducted on urban and rural elementary school students in Kupang City. One hundred and sixty students who met the inclusion and exclusion criteria were selected using consecutive sampling method. Characteristics data were collected by the interview, while the stunting data was known by measuring height and assessed by WHO anthroplus application, short-term memory data was obtained from digit span test. Stunting is a nominal data scale, while the short-term memory is an ordinal data scale. This study was analyzed bivariately using chi-square test with significant p value ≤ 0.05.Results: Chi-square test results of short-term memory between stunting and non stunting in urban and rural elementary school students obtained p = 0.144, which means there is no significant difference in short-term memory between stunting and non stunting in urban and rural elementary school children in Kupang.Conclusions: There is no significant difference in short-term memory between stunting and non stunting in elementary school children, both in urban and rural areas of Kupang.